Mastering Language Skills: Exploring Key Aspects In ELT (English Language Teaching) - Nurus Sufiyah Lailatul Hidayah; Faidatuz Zahroini Hasyim; Abidatul Azizah (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
English Language Teaching (ELT) plays a vital role in enabling language learners to achieve proficiency in English, a global lingua franca. This paper delves into the critical aspects of ELT, focusing on the exploration of key factors that contribute to successful language skill acquisition. The aim of this study is to shed light on the fundamental components that foster language mastery, encompassing listening, speaking, reading, and writing skills. In this research, we conduct a comprehensive review of relevant literature and empirical studies related to ELT and language skill development. By analyzing various theoretical frameworks and pedagogical approaches, we identify the essential elements that enhance language learning outcomes and promote effective teaching practices.